Public Service Spending: Efficiency and Distributional Impact - Lessons from Asia - Rouselle F. Lavado; Gabriel Angelo Domingo (Asian Development Bank (ADB), 2015)
Efficiency and equity are cornerstone concepts in rational service delivery in the public sector. This paper benchmarks efficiency and equity in public spending on health, education and social protection in a broad group of Asian Development Bank (ADB) member economies with varying levels of development. We describe public expenditure trends in health, education and social protection in the region. Following Herrera and Pang (2005), we conduct a formal efficiency benchmarking exercise using Data Envelopment Analysis and available input and output data from WDI, GFS, and ADB databases to deconstruct each member economy's efficiency changes in health and education spending. We next turn to review service provision inequality within ADB economies using utilization rates and benefit incidence, and note the deficiency of pro-poor spending in some sectors.
hdl:11540/5040
Keywords: H51; H52; H53; 330; governance and institutions; MDGs and inclusive growth; poverty; social protection